2021
DOI: 10.3389/fonc.2021.642134
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain Inhibition Attenuates the Progression and Sensitizes the Chemosensitivity of Osteosarcoma by Repressing GP130/STAT3 Signaling

Abstract: Osteosarcoma is the most common primary malignant bone tumor, and there are few ideal clinically available drugs. The bromodomain and extraterminal domain (BET) protein is an emerging target for aggressive cancer, but therapies targeting the BET in osteosarcoma have been unsuccessful in clinical trials to date, and further exploration of specific BET inhibitors is of great significance. In our study, we demonstrated that NHWD-870, a potent BET inhibitor in a phase I clinical trial, significantly inhibited tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…These genes show signi cant difference in the pro les of SCNA, expression, and methylation across three subgroups for both training and validation dataset, suggesting their potential roles in differentiating the OS patients. Among them, MLLT3[16], ATM(ataxia-telangiectasia mutated)/ATR (ataxia-telangiectasia and Rad3 related) [17][18][19], DDX10 [20][21][22], CASP1 [9] and BRD4 [23,24] and have been extensively studied and show to be associated with pathogenesis or clinical outcomes in osteosarcoma. Additionally, UBASH3B [25,26], CASP1 [27], CARM1[28-31], CHAF1B [32,33] and PCNT [34,35] have been studied in other cancers.…”
Section: Resultsmentioning
confidence: 99%
“…These genes show signi cant difference in the pro les of SCNA, expression, and methylation across three subgroups for both training and validation dataset, suggesting their potential roles in differentiating the OS patients. Among them, MLLT3[16], ATM(ataxia-telangiectasia mutated)/ATR (ataxia-telangiectasia and Rad3 related) [17][18][19], DDX10 [20][21][22], CASP1 [9] and BRD4 [23,24] and have been extensively studied and show to be associated with pathogenesis or clinical outcomes in osteosarcoma. Additionally, UBASH3B [25,26], CASP1 [27], CARM1[28-31], CHAF1B [32,33] and PCNT [34,35] have been studied in other cancers.…”
Section: Resultsmentioning
confidence: 99%
“…In OS, apatinib suppresses the OS cell growth, blocks cells in the G0/G1 phase, 231 and induces apoptosis and autophagy 232 . NHWD‐870 disrupts the binding affinity of BRD4 to the upstream receptor GP130 promoter region of STAT3, impairs upstream signaling, blocks STAT3 dimerization, and induces apoptosis 233 …”
Section: Mechanism Of Targeting Signaling Pathwaysmentioning
confidence: 99%
“… 232 NHWD‐870 disrupts the binding affinity of BRD4 to the upstream receptor GP130 promoter region of STAT3, impairs upstream signaling, blocks STAT3 dimerization, and induces apoptosis. 233 …”
Section: Mechanism Of Targeting Signaling Pathwaysmentioning
confidence: 99%
“…Previous studies have reported that BRD4 activates several downstream targets including the MAPK/ERK pathway, which regulates cell growth and differentiation. Additionally, BRD4 has been shown to interact with other proteins and transcription factors involved in cell proliferation, such as STAT3 [ 72 ].…”
Section: Pathophysiology Of Pahmentioning
confidence: 99%